Knowledge, Attitude, and Culture as The Main Determinants of The Referral Behavior of Pregnant Women in The Community Health Center of Sukosewu - Abdul Latip; Indrayanti Indrayanti; Mariya Ulfah (Humanistic Network for Science and Technology (HNST), 2021)
The high maternal mortality rate can be caused by the lack of referral behavior of pregnant women. The purpose of this study was to analyze the factors that influence the referral behavior of pregnant women. The design of this research is an analytic study with a cross sectional approach. The population were all pregnant womens in the working area of The Community Health Center of Sukosewu as many as 599 people. The sample size of 175 pregnant womens was selected using proportional random sampling technique. The independent variables were knowledge, attitude, accessibility, husband's support and culture. The dependent variable was the referral behavior of pregnant women. Collecting data using a questionnaire. Data were analyzed using logistic regression with p<0.05. The results indicate that there was an influence of knowledge (p=0.000), attitude (p=0.012), and culture (p=0.038) on the referral behavior of pregnant women. There was no effect of accessibility (p=0.490) and husband's support (p=0.377) on the referral behavior of pregnant women. Good knowledge, positive attitudes, and a strong culture can improve the referral behavior of pregnant women to facilitate the referral process for pregnant women to reach referral health facilities.Keywords: pregnant women; referral behavior; knowledge, attitudes, culture